National guidelines for capsule endoscopy: cost implications of non-compliance. (13th March 2011) - Cook, C; Hatton, C; Hendy, P; Makins, R
Abstract : Introduction: Capsule endoscopy (CE) is the investigation of choice to visualise the small intestinal mucosa. The British Society of Gastroenterology (BSG) published guidelines in 2008 concerning the use of CE. It recommended, in the setting of iron deficiency anaemia and obscure GI bleeding that all patients should have an upper GI endoscopy (OGD) and colonoscopy, if negative, further bleeding warranted a 'second-look' OGD. All patients with 2 negative OGDs and negative colonoscopy should undergo CE. The aim of this study was to assess local compliance with the BSG guidelines, and the cost implication of non-compliance. Methods: The authors retrospectively identified patients who had undergone CE at Gloucestershire Hospitals NHS Foundation Trust (GHNHSFT) over a 12-month period for the investigation of IDA and obscure GI bleeding. GHNHSFT is a split site 1000 bed district general hospital consisting of Gloucestershire Royal and Cheltenham General Hospitals, serving a population of 600 000 in a rural setting in the west of England. The authors identified all endoscopic and relevant radiological procedures the patients had undergone in relation to timing of CE to determine whether this complied with BSG guidelines. Results: 88 cases were identified. The hospital notes of 55 were available for scrutiny. The point at which CE should have been performed was determined (ie, after 2 OGDs and 1 colonoscopy, as stipulated above) and those patients who had undergone 'extra' endoscopies were identified. Also identified were the 'extra' admissions (ie, those that occurred after the CE should have been performed). The outcome of the CE was reviewed, with endoscopic findings graded on relevance. 8/55 (14.5%) patients had more than 2 OGDs (mean 1.69) there were a total of 16 excess OGDs. 12/55 patients (22%) had more than 1 colonoscopy (mean 0.56 as not all patients had a colonoscopy). There were a total of 17 'excess colonoscopies'. Other investigations included abdominal CT scanning (42 in total, 4 in 1 patient alone), barium studies (8 in 8 patients), CT angiography (2), Meckel's scan (1 study). There were 23 admissions, 7 of these in 5 patients after CE should have been performed. In all of the cases involving 'extra' admissions, the CE findings were highly relevant. The cost of a gastroscopy and colonoscopy was coded as £465 (550€) and £532 (630€) respectively; with total excess costs incurred by extra unnecessary endoscopy alone of £17 500 (20 000€). Estimation of excess admissions costs is difficult but assuming £500 per night, with on average a 3 night stay suggests an additional £10 500, an excess of £30 000 (€35 000). Conclusion: CE should be utilised early in the diagnostic pathway for iron deficiency anaemia as recommended by national guidelines. Delays and unnecessary repeated bidirectional endoscopy leads to unacceptable resource waste.